De novo genome assembly of Ansell's mole-rat (Fukomys anselli) - Bekavac, Milica; Coimbra, Raphael; Busa, Veronica F; Behm, Mikaela; Wagner, Rebecca E.; Goncalves, Angela; Begall, Sabine; Frye, Michaela; Odom, Duncan T (G3: Genes, genomes, genetics, 2026)
Ansell's mole-rat (Fukomys anselli) is an African rodent known for its subterranean lifestyle and unique phenotypic traits, including extreme longevity, magnetoreception, and a cooperative breeding social structure. Efforts to dissect the genetic architecture of these traits and to decipher their phylogenetic relationships within the broader African mole-rat family would greatly benefit from a reference-grade genome. Here, we report a first genome assembly of a male Ansell's mole-rat. By combining Oxford Nanopore Technologies long reads and Illumina short reads with Hi-C data, we generated a chromosome level assembly with a total length of 2.27 Gb, 412 scaffolds, and a scaffold N50 of 72.4 Mb. We identified 99.54% of expected genes and annotated 29,094 transcripts using RNA sequencing data. This high-quality de novo genome of F. anselli lays the foundation for dissecting the genetic and evolutionary basis of its extraordinary traits and resolving African mole-rat phylogeny.
Vorab veröffentlicht: 11. November 2025
Gesehen am 25.02.2026